2015
DOI: 10.1103/physreve.91.032114
|View full text |Cite
|
Sign up to set email alerts
|

Stochasticity enhances the gaining of bet-hedging strategies in contact-process-like dynamics

Abstract: In biology and ecology, individuals or communities of individuals living in unpredictable environments often alternate between different evolutionary strategies to spread and reduce risks. Such behavior is commonly referred to as "bet-hedging." Long-term survival probabilities and population sizes can be much enhanced by exploiting such hybrid strategies. Here, we study the simplest possible birth-death stochastic model in which individuals can choose among a poor but safe strategy, a better but risky alternat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…We found that, contrarily to 287 the well-mixed case, bet-hedging can be convenient in expanding populations. This 288 result complements the study in [52] for a fixed habitat and supports the view that communities can be optimal depending on the parameters. On the contrary, for fast 292 environmental changes, the optimal population always adopts a unique strategy.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…We found that, contrarily to 287 the well-mixed case, bet-hedging can be convenient in expanding populations. This 288 result complements the study in [52] for a fixed habitat and supports the view that communities can be optimal depending on the parameters. On the contrary, for fast 292 environmental changes, the optimal population always adopts a unique strategy.…”
supporting
confidence: 75%
“…Note that, in this model, the frequency of environmental change does not play a role, 122 as far as it is finite [52]. The physical reason can be understood from the right-hand 123 side of Eq.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, deterministic approaches neglect the effect of fluctuations, and these are now acknowledged to be both inherent and essential to the organization of communities of living systems [8]. On the one hand, the discreteness and finiteness of populations lead to demographic noise; which has been shown to be responsible of a wealth of non-trivial phenomena such as the emergence of complex statistical patterns in neutral communities [9,10], quasi-periodic oscillations in prey-predator systems [11], species formation [12], and others [13][14][15]. On the other hand, populations are strongly affected by fluctuations in external conditions [16,17], which in most of the cases are highly unpredictable.…”
Section: Introductionmentioning
confidence: 99%